PERAN UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM MEMPERJUANGKAN HAK PERLINDUNGAN DAN TUMBUH KEMBANG ANAK DI MALI TAHUN 2020 - Niwanda, Titis; Saeri, Mhd. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Mali has been a country in conflict since 1963. The ongoing conflict situation has had an impact on children, especially in the fulfillment of their children's rights. In 2019 Mali was ranked 184 out of 189 countries with low human resource development, one of the factors is the unequal access to protect growth and development. In 1946 UNICEF was established initially on a temporary basis, permanently inaugurated in 1953 with goals related to humanity and child empowerment. UNICEF itself is guided by the Convention on the Rights of the Child which regulates matters so that children get their rights and are treated fairly. This research uses the theory of the role of international organizations and the level of group analysis. This theory explains how the role of International Organizations in a problem includes a) initiator, b) facilitator, c) determinator and d) mediator. In this research, the initiator and facilitator factors supported by the UNICEF program are indicators that can fulfill children's rights in Mali. The research method used is a qualitative method with data collection techniques obtained from literature studies. International organizations related to children have carried out their role as facilitators with funding and initiators of cooperation carried out with various actors and non-governmental organizations with the same aim as UNICEF. UNICEF programs also support the fulfillment of children's rights in Mali in the fields of protection, education and health. Keywords: Children in Mali, Child Rights, Child Protection, Child Development, UNICEF